Pandangan Ibn Taimiyah Tentang Tasawuf dan Kaum Sufi - Nur, Syaifan (TAJDID, 2017)
This article tries to uncover the leading figure of Ibn Taimiyah as an Islam's most forceful theologians of tasawuf (Islamic Mysticism), beside his having great knowledge of other Islamic fields such as kalam (dogmatic theology), fiqh (Jurisprudence) or syariah (Religious Law), hadist (prophetic saying) and tafsir (the science of explanation of the Qur'an), or even in Islamic politics. Apart from that, this writing would like to clear up the issues concerning Ibn Taimiyah of whether or not he is really against tassawuh as in accordance with a great deal of observers's thought on him, or he himself has a particular thought on tassawuh. This writing tries to trace and uncover the Ibn Taimiyah's thought and outlook about the history of tassawuh development and a his criticism at Sufis at his time being considered exaggeratedly on the matter.